Radial motor nerve conduction study in posterior interosseous nerve syndrome and multifocal motor neuropathy - Baima, José Pedro S.; Heise, Carlos Otto (Arquivos de Neuro-Psiquiatria, 2025)
Background Finger extension weakness could be a presentation of either posterior interosseous nerve (PIN) syndrome or multifocal motor neuropathy (MMN). However, there is a delay in the diagnosis of MMN in cases with a selective radial weakness, as they are frequently misdiagnosed as PIN.Objective To analyze which variables in nerve conduction studies could aid in the early diagnosis of MMN.Methods We reviewed charts of patients with diagnoses of MMN or PIN syndrome, from 2014 to 2022, in a single Brazilian reference center. Electrophysiological parameters included in the analysis were motor conduction velocity (CV), the presence and magnitude of conduction block (CB), distal motor latencies (DML), and the compound muscle action potential amplitude (CMAP) of the affected radial nerve.Results A total of 44 radial nerves were included in the study. Axonal loss was associated with a diagnosis of PIN syndrome, while conduction block was associated with MMN (p < 0.05). No patient with PIN had a CB over 60%, while 7 out of 12 radial CB blocks in patients with MMN were above that. Axonal degeneration was present in 4 MMN patients and in all patients with PIN syndrome. There was no difference in CV and DML between groups.Conclusion The presence of CB or the absence of distal CMAP amplitude reduction should lead physicians to consider MMN, and a comprehensive nerve conduction study should be performed.
Keywords: Peripheral Nervous System Diseases; Radial Neuropathy; Nerve Compression Syndromes; Electromyography